2022
DOI: 10.3390/foods11213325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Tannic Acid on Obesity and Gut Microbiota in C57BL/6J Mice Fed with High-Fat Diet

Abstract: Dietary tannic acid, as a natural polyphenolic, has many important biological activities. This study aimed to investigate the effect of dietary tannic acid on obesity and gut microbiota in mice with a high-fat diet. Male C57BL/6J mice fed a high-fat diet were treated with dietary tannic acid for eight weeks. Results showed that dietary tannic acid reduced the body weight gain, regulated glycolipid metabolism, improved the insulin resistance, and attenuated the liver oxidative stress in high-fat diet-fed mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…It was also found that tannic acid could alleviate oxidative stress in high-fat diet mice. 32 Notably, the mixtures had a more profound effect than tannic acid or resistant starch alone. In summary, oxidative stress resistance was in the order of the MRT group > the HRT group > the TA group > the LRT group > the RS group.…”
Section: Oxidative Stress Resistancementioning
confidence: 99%
“…It was also found that tannic acid could alleviate oxidative stress in high-fat diet mice. 32 Notably, the mixtures had a more profound effect than tannic acid or resistant starch alone. In summary, oxidative stress resistance was in the order of the MRT group > the HRT group > the TA group > the LRT group > the RS group.…”
Section: Oxidative Stress Resistancementioning
confidence: 99%
“…LPS was subcutaneously injected into mice in the control group fed with normal diet. After 4 weeks, mice in the control group became obese and produced insulin resistance (Fang et al, 2022).…”
Section: Gut Microbiota and Chronic Inflammationmentioning
confidence: 99%
“…The pharmacological potential of these plants, based on their phytochemical compounds, can aid in restoring the body's redox balance [27] and chronic conditions [28,29]. Some metabolites that have biological effects related to the context of obesity and its complications are tannins [30,31], coumarins [32,33], terpenoids [34], anthocyanins [35,36], saponins [37], phenolic compounds, and flavonoids [38].…”
Section: Chemical Constitution Of Native Plants Of the Brazilian Cerradomentioning
confidence: 99%